INDIGENOUS TRICHODERMA SPP. COLLECTED FROM SHALLOT FIELDS SUPPRESS FUSARIUM ROT DISEASE - Mohammad Yunus; Nur Edy; Vinsensia Pato; Moh. Hibban Toana; Johanis Panggeso; Flora Pasaru; Asrul Asrul (Universitas Tadulako, 2019)
Antagonist fungi have enormous potential to be a biological agent to control Fusarium basal rot (FBR) disease in shallot. This study aims to explore, isolated, and tested the antagonistic of Trichoderma sp. indigenous isolated from shallot fields against FBR disease. Exploration of isolates was carried out at the shallot planting center in Sigi Regency. The isolation characterization and inhibition tests were carried out at the Laboratory of Plant Pathology Tadulako University. The inhibition test was using two culture methods. The results showed that there were Trichoderma sp. obtained from shallot fields in the village of Sidera. In vitro test results showed Trichoderma sp., which was found to be able to inhibit the growth of the fungus F. oxysforum. The highest inhibition reached 69.18% within six days. As a comparison of inhibition of Trichoderma harzianum, a laboratory collection, within 6 days only reached 61.06%. Trichoderma sp. the origin of shallot fields was more effectively used as a biological agent in controlling FBR disease.